Effectiveness of Rosella Flower Syrup on Blood Pressure in Hypertensive Patients with Cholesterolemia - Annas Masykur; Pujiastuti, Rr. Sri Endang; Ta’adi, Ta’adi (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Hypertension is one of the causes of repeated morbidity and mortality worldwide. Basic Health Research (Riskesdas) shows an increase in the prevalence of hypertension in Indonesia with ages 18 years and over, from 25.8% in 2013 to 34.1% in 2018. Rosella Flower Syrup, which contains flavonoids ± 40 mg / 4 grams of rosella extract dissolved in 5 ml of distilled water, reduces blood pressure. This research aims to determine whether a 5 ml rosella flower syrup combined with antihypertensive drugs and simvastatin can reduce blood pressure in hypertensive patients with cholesterolemia. This true experimental study used a pre-test and post-test control group design. Forty-eight respondents were selected using the stratified random sampling method through the probability sampling technique. They were divided into two groups; the control group was only given antihypertensive drugs and simvastatin; meanwhile, the intervention group was combined with a 5 ml rosella flower syrup. Rosella flower syrup 5 ml combined with antihypertensive and simvastatin for 14 days can reduce systolic blood pressure (p = 0.000) and diastolic blood pressure (p = 0.033), which means there was a significant difference between the two groups. The conclusion is that five 5ml of Rosella flower syrup combined with antihypertensive drugs and simvastatin can reduce systolic and diastolic blood pressure compared to taking antihypertensive drugs and simvastatin alone. Future research is expected to increase the dose of rosella flower syrup for more than 14 days to get more effective results.